Cell-free layer measurements ofin vitroblood flow in a microfluidic network: an automatic and manual approach - Bento, David (2020)
In microcirculation, the cell-free layer (CFL) is a well-known physiological phenomenon that plays an important role in reducing the flow resistance and in balancing nitric oxide (NO) production by endothelial cells and NO scavenging by red blood cells. To better understand this phenomenon, several blood flow studies have been performed in simple geometries at both in vivo and in vitro environments. However, to date little information is available regarding the effects imposed by a complex branching network on the CFL. The present study shows the CFL layer variation at a microchannel network. The images were captured using a high-speed video microscopy system and the thickness of the CFL was measured using both manual and automatic image analysis techniques. Using this methodology, it was possible to visualise the in vitro blood flowing through the network and to identify several flow phenomena that happen in microcirculation. Overall, the results have shown that the concentration of cells and the geometrical configuration of the network have a major impact on the CFL thickness. In particular, the thickness of the CFL decreases as the fluid flows through a microchannel network composed with successive smaller channels. It was also clear that, for the full length of the network, the CFL thickness tends to decrease with the increase of the concentration of cells. The automatic method developed becomes inaccurate for high haematocrit and needs be calibrated by manual methods for Hcts bigger than 10%. The results obtained from this study could help the development and validation of multiscale numerical models able to take into account the CFL for simulating microvascular blood flow.